Effect of catfish’ (Clarias gariepinus) flour and oil with probiotic Enterococcus faecium IS-27526 based functional feed provision on bodyweight and C-reactive protein (CRP) of aged atherogenic female Cynomolgus monkey (Macaca fascicularis) (Microbiology Indonesia, 2016)
The aim of the research was to study the effect of functional feed of catfish’ flour, oil and probiotic E. faecium IS-27526 based on bodyweight and CRP (C-reactive protein) of aged female Cynomolgus monkey (Macaca fascicularis). Nine aged female Cynolmolgus randomly divided into three groups. The age is determined by dentition, with bodyweight in a range of  2 – 4 kg. Animals were placed in individual cages in the position where they can interact audiovisually. Feed composition consists of sugar, egg, soy flour, wheat flour, sweet potato flour, butter, egg yolk flour, catfish’ flour and oil, and microencapsulated probiotic Enterococcus faecium IS-27526 and administered for 90 days. Evaluation of bodyweight (BW) and CRP were conducted. There is no significant effect (p>0.05) of experimental diets on bodyweight in each group. However, probiotic tends to delay the bodyweight gain. The bodyweight of cynomolgus in probiotic diet is shown more stable than others. There is no the effect of experimental diets on CRP which is marked by negative result of CRP test. Probiotic E. faecium IS-27526 is potential for bodyweight homeostasis regulation to reduce the risk of overweight and obesity.